2016
DOI: 10.1080/13698575.2016.1229758
|View full text |Cite|
|
Sign up to set email alerts
|

From scientific article to press release to media coverage: advocating alcohol abstinence and democratising risk in a story about alcohol and pregnancy

Abstract: In this article, we follow the approach taken by Riesch and Spiegalhalter in “Careless pork costs lives’: Risk stories from science to press release to media’ published in this journal, and offer an assessment of one example of a ‘risk story’. Using content and thematic qualitative analysis, we consider how the findings of an article ‘Fetal Alcohol Exposure and IQ at Age 8: Evidence from a Population-Based Birth-Cohort Study’ were framed in the article itself, the associated press release, and the subsequent e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Instead, scientific findings had been interpreted and reported by journalists and news reporters. In order to raise the readability for the lay public, however, the media agencies had to simplify research findings by reducing some nuance, sometimes at the cost of exaggerating and misrepresenting the findings (Lee et al, 2016). By communicating their findings to the lay public themselves, scientists have the opportunity to summarize their findings as accurately as possible, which can forestall misrepresentations and misinterpretations introduced by intermediaries.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, scientific findings had been interpreted and reported by journalists and news reporters. In order to raise the readability for the lay public, however, the media agencies had to simplify research findings by reducing some nuance, sometimes at the cost of exaggerating and misrepresenting the findings (Lee et al, 2016). By communicating their findings to the lay public themselves, scientists have the opportunity to summarize their findings as accurately as possible, which can forestall misrepresentations and misinterpretations introduced by intermediaries.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns have been raised that the media’s reporting of health science is sensationalist, inaccurate, and undermines the intended messaging of the scientific community 1 , 3 , 7 , 8 . A number of studies have examined the role of PRs in science communication, and found they may be responsible, especially through the removal of caveats or the framing of correlational associations as causative 1 , 2 , 7 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Concerns have been raised that the media’s reporting of health science is sensationalist, inaccurate, and undermines the intended messaging of the scientific community 1 , 3 , 7 , 8 . A number of studies have examined the role of PRs in science communication, and found they may be responsible, especially through the removal of caveats or the framing of correlational associations as causative 1 , 2 , 7 9 . While a certain degree of interpretation is necessary for PRs to fulfil their bridging function, such changes in the framing of risk messages at the PR stage are likely to later influence their public interpretation and reception, and therefore risk a detrimental impact on public health 2 , 4 , 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The topic of parenthood and parenting has gathered considerable social and academic interests, as an increasing number of parenting practices such as conceiving, breastfeeding, playing and safeguarding, previously deemed private, are now subject to intense public debate (Lupton, 2008;Murray, 2015;Murphy, 2000;Furedi, 2008;Lee et al, 2010;Beck-Gernsheim, 1995). While a wealth of literature researching parenthood, parental practices and parenting culture can be found in Western societies (Oakley, 1980;Apple, 1995;Shirani et al, 2012;Lee et al, 2016;Schmied and Lupton, 2001;Lee et al, 2010;Thomson et al, 2011;Murphy, 2000;Furedi, 2008;Knaak, 2010;Hays, 1996;Crighton et al, 2013), little existent literature addresses similar topics in China, a country with a recent history of state-directed modernisation. The modernising processes including individualisation, marketisation and a neoliberal reform of the health care system have reconfigured the 'cultural experience' of individuals (Barker, 2012: 185)…”
Section: Introductionmentioning
confidence: 99%
“…The topic of parenthood and parenting has gathered considerable social and academic interest, as an increasing number of parenting practices such as conceiving, breastfeeding, playing and safeguarding, previously deemed private, are now subject to intense public debate (Beck-Gernsheim, 1995; Furedi, 2008; Lee et al, 2010; Lupton, 2008; Murphy, 2000; Murray, 2015). While a wealth of literature researching parenthood, parental practices and parenting culture can be found in Western societies (Apple, 1995; Crighton et al, 2013; Furedi, 2008; Hays, 1996; Knaak, 2010; Lee et al, 2010, 2016; Murphy, 2000; Oakley, 1980; Schmied and Lupton, 2001; Shirani et al, 2012; Thomson et al, 2011), little existing literature addresses similar topics in China, a country with a recent history of state-directed modernisation. The modernising processes - including individualisation, marketisation and a neoliberal reform of the healthcare system - have reconfigured the ‘cultural experience’ of individuals (Barker, 2012: 185), such as parents shifting their childrearing activities towards a modern, self-managed set of practices based on individual family resources (Binah-Pollak, 2014; Davis and Sensenbrenner, 2000; Gong, 2016).…”
Section: Introductionmentioning
confidence: 99%